Digital Financial Management and Financial Accountability in Community Learning Centers: The Mediating Role of BOS Fund Management Effectiveness - Abubakar Abubakar; Reza Ahmad Madani; Taufani C. Kurniatun; Eka Prihatin; Abubakar; Reza Ahmad Madani; Taufani C. Kurniatun (Universitas Negeri Malang, 2026)
The increasing demand for transparent and accountable financial governance has encouraged educational institutions to adopt digital financial management systems. However, empirical evidence explaining how digital financial systems improve accountability through organizational management processes remains limited, particularly in Community Learning Centers (CLC). This study aimed to examine the effects of the ARKAS application system on the effectiveness and accountability of fund management of Bantuan Operasional Sekolah (BOS), as well as the mediating role of management effectiveness. A quantitative survey was conducted involving 62 members of BOS fund management teams from CLC in Bandung Regency, Indonesia, selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using descriptive statistics, multiple regression, path analysis, and the Sobel test. The results revealed that the ARKAS application system significantly improved both the effectiveness and accountability of BOS fund management. Furthermore, management effectiveness significantly enhanced accountability and mediated the relationship between the ARKAS application system and accountability. These findings imply that CLC should integrate digital financial management with continuous managerial capacity development to strengthen financial governance. The study contributes to educational financial management literature by demonstrating that management effectiveness constitutes the organizational mechanism through which digital financial systems enhance accountability in non-formal education.